Manufacture and Analysis of Activated Carbon from Rubber Fruit Shell with Chemical and Physical Processing - Lisna Efiyanti; Suci Aprianty Wati; Mamay Maslahat (Jurnal Ilmu Kehutanan)
The utilization of activated carbon in Indonesia is increased, which is in line with the increase of activated carbon needs, therefore it is necessary to search the raw materials and methods continuously for good quality activated carbon. One of the raw materials that can be used to produce activated carbon is a rubber fruit shell because it is not properly utilized. In this research, activated carbon was made from rubber fruit shells by the steam activation method at a temperature of 650°C, 10% potassium hydroxide, and 10% phosphoric acid activation. The activated carbon was then analyzed using SNI 06-3730-1995 methods with parameters of water content, ash content, volatile matter content, fixed carbon content, iod adsorption, methylene blue adsorption, and benzene adsorption. The functional groups, crystallinity, and morphology of activated carbon also analyzed using FTIR, XRD, and SEM respectively. The results shows that the water content, ash content, volatile matter content, fixed carbon content, iod adsorption, methylene blue adsorption, and benzene adsorption are 1,83-3,74%; 2,86-8,14; 7,36-13,55; 82,8-89,78%; 355,21-569,39 mg/g; 10,34-17,61 mg/g; 8,09-19,26%, respectively. The FTIR results from activated carbon are contain of several functional groups, like OH; CH aliphatic, CH aromatic, C=O; C-C; C=C and C-O, meanwhile the degree of crystallinity from activated carbon formed are ranged 11,34-30,78% with 5-9 μm of pore size. The activated carbon with KOH activator has good adsorption in iod and methylene blue compound meanwhile activated carbon from steam activation can be a good adsorbent on the benzene compound.